Dukungan sosial orangtua anak tunarungu usia 11 tahun di SDN Perwira Kota Bogor - Shara Syah Putri; Asep Supena; Durotul Yatimah (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2019)
This study was conducted to describe the social support of deaf parents starting from, social support of parents in educating deaf children and the impact of the application of parental social support to deaf children. This research is based on the observation of an 11-year-old child, conducted since September 2018 until January 2019, with some data acquisition since 2014. This research was conducted using a qualitative approach with a case study method. Collecting data through observation, interviews and documentation studies. The purpose of this study was to describe the social support of deaf parents starting from parental social support in educating deaf children and the impact of the application of parental social support to deaf children. The findings in this study contained five forms of parental social support, including information support, emotional, instrumental, social networking, assessment and appreciation for deaf children.